Occurrence of Hybrid Escherichia coli Strains Carrying Shiga Toxin and Heat-Stable Toxin in Livestock of Bangladesh - Johura, Fatema-Tuz; Parveen, Rozina; Islam, Atiqul; Sadique, Abdus; Rahim, Md Niaz; Monira, Shirajum; Khan, Anisur R.; Ahsan, Sunjukta; Ohnishi, Makoto; Watanabe, Haruo; Chakraborty, Subhra; George, Christine M.; et al. (Frontiers in Public Health, 2017)
Shiga-toxin producing Escherichia coli (STEC) and enterotoxigenic E. coli (ETEC) are important causes of diarrhea in humans and animals worldwide. Although ruminant animals are the main source of STEC, diarrhea due to this pathotype is very low in Bangladesh where ETEC remains the predominant group associated with childhood diarrhea. In the present study, E. coli strains (n=35) isolated from Bangladesh livestock (goats, sheep and cattle) and poultry (chicken and ducks) were analyzed for the presence of major virulence factors such as Shiga toxins (STX-1 and STX-2), heat-labile toxin (LT), and heat-stable toxins (STa and STb). Multiplex polymerase chain reaction (PCR) results revealed 23 (66%) E. coli strains to be virulent possessing either sta (n=5), stx (stx1, n=8; stx2, n=2), or both (n=8) genes in varying combinations. Thirty four percent (8/23) of strains from livestock were hybrid type that carried both stx (either stx1 or stx2) and ETEC-specific enterotoxin gene sta. Serotyping results revealed that the ETEC strains belonged to five serotypes, namely O36:H5, O174: H-, O152:H8, O109:H51, and O8:H21, while the STEC-producing strains belonged to serotypes O76:H19 (n=3), O43:H2 (n=2), O87:H16 (n=2), OR: H2 (n=1), O110:H16 (n=1) and O152:H8 (n=1). The STEC-ETEC hybrid strains belonged to serotypes O76:H19 (n=3), O43:H2 (n=2), O87:H16, OR: H2 and O152:H8. Forty percent (2/5) of the ETEC and 20% (2/10) of the STEC strains were multidrug resistant with the highest drug resistance (50%) being found in the hybrid strains. Molecular fingerprinting determined by pulsed-field gel electrophoresis (PFGE) and cluster analyses by dendrogram revealed that genetically, STEC-ETEC hybrid strains were highly heterogeneous. Multi-drug resistant E. coli STEC-ETEC hybrid strains in domesticated animals pose a public health threat for humans in Bangladesh.